PENGARUH LINGKUNGAN BELAJAR DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA (STUDI KASUS PADA SISWA KELAS XI SMK TELKOM BANDUNG) - Rida Dwi Widiastuty; Ary Ferdian; Daduk Merdika Mansur (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
Based on data from midterm tests 2020/2021, student achievement of SMK Telkom Bandung has not met the minimum completeness criteria with a percentage of 43% of the total of 146 students. The results of attendance data indicate that student learning motivation is not optimal due to fluctuations, as well as the learning environment is not optimal due to changes in learning activities carried out at this time. This study aims to show the influence of the learning environment and learning motivation on student achievement in class XI SMK Telkom Bandung either simultaneously or partially. The research method used in this research is quantitative method. The data collection technique in this research used questionnaires with the Proportionate Stratified Random Sampling technique, so that the questionnaire was distributed to respondents with a total of 185 students. Based on the results of this study and the results of the respondents, the variables of the learning environment, learning motivation and student achievement are at the "High" category level. Suggestions that can refer to the results of the research are to improve the communication of teachers to students so that students are motivated by their learning activities so as to improve students' ability, thinking and analysis, as well as skills and coordination between educators / teachers and parents in encouraging students to have high motivation in learning activities at home, supervising every learning activity taking place.